2007
DOI: 10.1016/j.febslet.2007.07.068
|View full text |Cite
|
Sign up to set email alerts
|

The GluCre‐ROSA26EYFP mouse: A new model for easy identification of living pancreatic α‐cells

Abstract: The control of glucagon secretion by pancreatic acells is poorly understood, largely because of the difficulty to recognize living a-cells. We describe a new mouse model, referred to as GluCre-ROSA26EYFP (or GYY), allowing easy a-cell identification because of specific expression of EYFP. GYY mice displayed normal glycemic control during a fasting/refeeding test or intraperitoneal insulin injection. Glucagon secretion by isolated islets was normally inhibited by glucose and stimulated by adrenaline. [Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 32 publications
7
87
1
Order By: Relevance
“…For liver timeseries experiments, livers were isolated from CD1 mice, stored overnight at 4°C in RNAlater (Ambion), and then stored at À80°C. Mouse pure beta-cells were purified from islets of RIPYY mice expressing EYFP under the rat insulin promoter, i.e., specifically in beta-cells (Quoix et al 2007). Additional details on tissue preparation and RNA extraction are provided in the Supplemental Material.…”
Section: Methods Preparation Of Tissues and Purified Cellsmentioning
confidence: 99%
“…For liver timeseries experiments, livers were isolated from CD1 mice, stored overnight at 4°C in RNAlater (Ambion), and then stored at À80°C. Mouse pure beta-cells were purified from islets of RIPYY mice expressing EYFP under the rat insulin promoter, i.e., specifically in beta-cells (Quoix et al 2007). Additional details on tissue preparation and RNA extraction are provided in the Supplemental Material.…”
Section: Methods Preparation Of Tissues and Purified Cellsmentioning
confidence: 99%
“…Indeed, it has been proposed that a pro-α cell population exists as a facultative progenitor that exhibits features of β and α cells in mammals (Habener and Stanojevic, 2012), although this proposition contradicts earlier lineage-tracing studies (Herrera, 2000) that showed that mature β and α cells arise from distinct lineages. As ∼20-65% of α cells are not marked in glucagon:Cre transgenic mice (Herrera, 2000;Quoix et al, 2007;Magnuson and Osipovich, 2013;Mastracci et al, 2013), it is possible that relevant subpopulations of α cells have gone undetected in these studies. The development of novel mouse and zebrafish transgenic strains in which Cre is more faithfully regulated by the endogenous glucagon locus might shed light on this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may explain this lack of information about glucagon secretion. First, the scarcity of this cell population in islets of animal models such as mice and rats along with several technical limitations of conventional methods have made it more difficult to study a-cells than b-cells (Quoix et al 2007). Second, the lack of functional identification patterns has also been an important limitation in a-cell research.…”
Section: Introductionmentioning
confidence: 99%